ANALISIS DAMPAK PROGRAM KELUARGA HARAPAN TERHADAP UPAYA PENGENTASAN KEMISKINAN DAN KESEJAHTERAAN MASYARAKAT DI DESA PAMUTUH KECAMATAN LEBAKBARANG - Helena Angel likha; Muhammad Aris Safi’i; Hendri Hermawan Adinugraha (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2025)
This research aims to analyze the impact of the Family Hope Program (PKH) in efforts to eradicate poverty and improve community welfare in Pamutuh Village, Lebakbarang District. Using a qualitative approach, this research focuses on evaluating access to education and health services, as well as their impact on changes in the socio-economic behavior of beneficiaries. The research results show that PKH makes a significant contribution in increasing children's educational participation, access to health services, and stability of family income. This program not only provides financial assistance, but also encourages positive behavioral changes that help break the intergenerational cycle of poverty. By using Amartya Sen's capability theory, this research emphasizes the importance of increasing individual capabilities as the main factor in societal welfare. Even though it is effective, PKH still faces challenges such as obtaining recipient data which needs to be improved so that this program is more optimal. It is hoped that these findings can become a reference for social policies in alleviating poverty in a more sustainable manner.